ANALISIS JARINGAN TRANSMISI AIR BAKU ULUNGGOLAKA DENGAN MENGGUNAKAN SOFTWARE EPANET 2.0 - Dany Kusnadi Herlambang; Fathur Rahman Rustan; Erika Aprianti (PRODI D3 TEKNIK SIPIL, 2018)
Water is a very important need for human survival. Without water there would be no life on earth. In urban areas, water supply system doing by piping system and non piping system. The piping system is managed by Perusahaan Daerah Air Minum (PDAM) and non-piped system is managed by the community either individually or in groups. The condition of distribution for clean water in Ulunggolaka Village, Kolaka District is still inadequate. So in order to meet the availability of water for the needs of the community, it is necessary to do the distribution of clean water by using pipes as transmission media.The purpose of this research was to know the amount of raw water requirement in Ulunggolaka Village, and to simulate Ulunggolaka raw water transmission pipeline network.From the results of the research, water demand in 2018 was 1.222 liters / second with the projection of population of 2,513 people, and the projection of population in 5 years ie 2023 obtained by water requirement 1,414 liter / second with population 2,909 person. Based on Epanet 2.0 simulation results obtained the highest pressure is at node 4 and the lowest was at node 2. The highest flow rate and energy loss are in pipe 4 while the lowest flow rate was in pipe 5 and the lowest energy loss was in pipe 3.